Spatiotemporally homogeneous crystallization for ambient scalable perovskite photovoltaics - Binlou Gao; Yang Zhong; Xiao Luo; Jiacheng He; Junxi Guo; Xueying Wang; Yikun Liu; Licheng Tan; Yiwang Chen (Science, 2026)
Commercializing perovskite solar cells (PSCs) will likely require the scalable deposition of homogeneous perovskite films under ambient conditions. However, the spatially heterogeneous degradation of metastable perovskites during prolonged coating leads to nonuniformity. Here, we demonstrate spatiotemporally homogeneous crystallization of α-phase FAPbI 3 (where FA is formamidinium) enabled by a phase-locking strategy that establishes a dynamically evolving, moisture-buffering intergranular network during large-area printing. This method prevents the premature degradation caused by ambient humidity, eliminating directional inhomogeneity. Blade-coated PSCs achieved a 26.7% power conversion efficiency (PCE; 26.1% certified), and rigid and flexible 100-square-centimeter modules reached 21.5 and 19.5%, respectively. Improved morphological homogeneity mitigated localized degradation and suppressed self-amplifying aging pathways. Encapsulated devices retained more than 90% of their initial PCE after 1500 hours of 85°C maximum power point tracking in ambient air.